CCS technology: overview of projects, technology and monitoring (Rudarsko-geološko-naftni zbornik, 2018)
Carbon capture and storage (CCS) in terms of geological sequestration presents the process of capturing CO2 from large point sources, transporting it to a storage site, and depositing it into an underground geological formation.In addition to ecological benefits, underground injection of CO2 shows certain potential risks associated with unwanted migration of CO2 to groundwater and surface, so the possibility of carrying out such projects depends on the possibility of reducing mentioned risks to an acceptable level. For this purpose, a detailed risk assessment and analysis must be carried out, serving as the basis for a monitoring plan. Well designed and implemented monitoring plan and program provide important data on site integrity, well injectivity, and entire storage complex performance.This paper gives the overview of large scale and pilot projects of CO2 capture and geological storage in operation, under construction and in the phase of development all over the world, technology basics and available monitoring techniques. An example of CCS project monitoring is given through the monitoring program of the Lacq pilot project in France